KEBERSYUKURAN DAN KEPUASAN DALAM PERNIKAHAN: SEBUAH TINJAUAN PSIKOLOGIS PADA WANITA DEWASA MUDA - Khairani, Maya; Rachmatan, Risana; Sari, Kartika; Soraiya, Putri (INTERNATIONAL JOURNAL OF CHILD AND GENDER STUDIES, 2016)
Gratitude is a value that is taught universally, either in religion or culture that surrounds us. Previous studies have demonstrated an association between gratitude with quality of long-term relationships such as romantic relationships, like marriage. This study aim to provide the description of the level of gratitude in marriage and marital satisfaction on early adult woman in Banda Aceh. This study uses a quantitative method by using purposive sampling. Methods of data collection in this study using The Gratitude Questionnaire-6 (GQ-6, which consists of 6 questions) and Enrich Marital Satisfaction (EMS, which consists of 15 questions). There are 93 early adult women participated on this study with characteristics between 20-40 years old, already have children, and have been married for 10 years maximum. Based on the results found that the gratitude’s average score is 35.6 with a standard deviation 3.67 and the marital satisfaction’s average score is 53.53 with standar deviation 9.36 . The result of this study shows that most early adult women in Banda Aceh has moderate level of gratitude and marital satisfaction.